Lack of motor recovery after prolonged denervation of the neuromuscular junction is not due to regenerative failure. (28th September 2015) - Sakuma, Miyuki; Gorski, Grzegorz; Sheu, Shu‐Hsien; Lee, Stella; Barrett, Lee B.; Singh, Bhagat; Omura, Takao; Latremoliere, Alban; Woolf, Clifford J.
Abstract: Motor axons in peripheral nerves have the capacity to regenerate after injury. However, full functional motor recovery rarely occurs clinically, and this depends on the nature and location of the injury. Recent preclinical findings suggest that there may be a time after nerve injury where, while regrowth to the muscle successfully occurs, there is nevertheless a failure to re‐establish motor function, suggesting a possible critical period for synapse reformation. We have now examined the temporal and anatomical determinants for the re‐establishment of motor function after prolonged neuromuscular junction (NMJ) denervation in rats and mice. Using both sciatic transection–resuture and multiple nerve crush models in rats and mice to produce prolonged delays in reinnervation, we show that regenerating fibres reach motor endplates and anatomically fully reform the NMJ even after extended periods of denervation. However, in spite of this remarkably successful anatomical regeneration, after 1 month of denervation there is a consistent failure to re‐establish functional recovery, as assessed by behavioural and electrophysiological assays. We conclude that this represents a failure in re‐establishment of synaptic function, and the possible mechanisms responsible are discussed, as are their clinical implications. Abstract : Existence of a critical period to re‐establish functional NMJ after nerve trauma. 1) If muscles are denervated less than 30 days motor fibers reach NMJ and this is associated with motor function. 2) After 38 days, fibers can still grow into the tissue and form structural NMJ, but no muscle activity occurs. 3) Very prolonged denervation (> 2 months) causes the milieu to become non‐permissive for nerve growth, which eventually leads to a loss of NMJ. If muscles are denervated less than 30 days motor fibers reach NMJ and this is associated with motor function. After 38 days, fibers can still grow into the tissue and form structural NMJ, but no muscle activity occurs. Very prolonged denervation (> 2 months) causes the milieu to become non‐permissive for nerve growth, which eventually leads to a loss of NMJ.